Law and practice of EU external relations: salient features of a changing landscape - Dashwood, Alan (Cambridge Univ. Press, 2009)
Direct effect and interpretation of international agreements in the recent case law of the European Court of Justice / Francis Jacobs -- Defining competence in EU external relations : lessons from the constitutional treaty / Marise Cremona -- Article 47 TEU and the relationship between first and second pillar competences / Alan Dashwood -- EC law and UN Security Council Resolutions : in search of the right fit / Piet Eeckhout -- Fundamental rights and the interface between second and third pillar / Eleanor Spaventa -- The EU as a party to international agreements : shared competences?; mixed responsibilities? / Ramses Wessel -- Will the common commercial policy be impeded by non-ratification of the constitutional treaty? / Peter-Christian Müller-Graff -- The extent to which the EC legislature takes account of WTO obligations : jousting lessons from the European parliament / Jacques Bourgeois and Orla Lynskey -- The relations between the EU and Switzerland / Christine Kaddous -- The relations between the EU and Andorra, San Marino and Monacomarc Maresceau -- The EU's neighbourhood policy towards Eastern Europechristophe Hillion -- The four common spaces : new impetus to the EU-Russia stategic partnership? / Peter van Elsuwege -- The EU's strategic partnership with the Mediterranean and the Middle East : a new geopolitical dimension of the EU's proximity strategies / Erwan Lannon -- The EU's transatlantic relationship / Günter Burghardt -- With eyes wide shut : the EC strategy to enforce intellectual property rights abroad / Inge Govaere -- EU environmental law and its green footprints in the world / Kirstyn Inglis
Includes bibliographical references and index
Keywords: European Union countries -- Foreign relations; European Union -- Foreign relations; Aufsatzsammlung; Recht; Außenpolitik; Europäische Union